The Longest Day : June 6, 1944 - Ryan, Cornelius (Lodon Vigtor Gollangz Ltd, 1962)
Operation Overlord the Allied invasion of Europe, began at fifteen minutes after midnight on June 6, 1844-in the first hour of a day that would be forever known as D Day. The pathfinders jumped out of their planes over Normandy, the men who were to light the dropping zones for the paratroopers and infantry.
Include Illustrations, Bibliography and Index.
Keywords: World War (1939-1945) -- Military campaigns -- France--Normandy